The relationship between inhibitory control and speech production in young multilinguals - Krzysik, Iga (Yearbook of the Poznan Linguistic Meeting, 2020)
Speech production in multilinguals involves constant inhibition of the languages currently not in use. In relation to phonological development, higher inhibitory skills may lead to the improved suppression of interference from the remaining languages in one’s repertoire and more accurate production of target features. The participants were 20 sequential multilingual learners (13-year-olds with L1 Polish, L2 English, L3 German), acquiring their L2 and L3 by formal instruction in a primary school. Inhibition was measured in a modified flanker task (Eriksen & Eriksen 1974; Poarch & Bialystok 2015). Multilingual production of voice onset time (VOT) and rhotic consonants was tested in a delayed repetition task (e.g. Kopečková et al. 2016; Krzysik 2019) in their L2 and L3. The results revealed that higher inhibitory control was related to increased global accuracy in the L2 and L3 production. Moreover, higher inhibitory control was also linked to higher accuracy in the overall L2 production, but there was no significant relationship with the L3 accuracy. These findings suggest that inhibition may play a role in phonological speech production, however, it may depend on one’s level of proficiency.